Pengaruh Luas Lahan, Penggunaan Pestisida, Tenaga Kerja, Pupuk Terhadap Produksi Kopi di Kecamatan Pekutatan Kabupaten Jembrana - Ambarita, Jerry Paska; Kartika, I Nengah (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
F armers in Indonesia amounted to approximately 46.7 million people, or 44 percent of the total workforce. Look of absolute value, the agricultural sector provides a large amount of contribution to the increase in GDP, but in fact, when viewed through a map of poverty in Indonesia, it seems certain that the largest part of the population who are poor are working in the agricultural sector (Tambunan, 2003: 23 ). This condition causes the agricultural sector should be able to push yourself to be able to increase their agricultural products. The purpose of this study is 1. To determine the effect of the use of factors production land, pesticide, fertilizer, and labor costs to total production of cofee seed in the district Pekutatan as collective data. 2 To determine the effect of the use of factors production land, pesticide, fertilizer, and labor costs to total production of cofee seed in the district Pekutatan as separated data. And 3, to determine the most infkuence variable of the factors production land, pesticide, fertilizer, and labor costs of cofee seed in the district Pekutatan. In this study , the type of data used is in the form of primary data is data that has been collected by researcher in observaton. In this case such a data rate of production, land, pesticide, fertilizer, and labor costs to total production of cofee seed in the district Pekutatan. The analysis used in this study is multiple linear regression analysis. Linear Regression analysis is used to quantify the effect of more than one predictor variables (independent variables) on the dependent variable. Land area, the use of pesticides, labor, fertilizer effect simultaneously and partially on coffee production in Sub Pekutatan Jembrana.
Keywords: Productivity; Land; Pesticide; Labor; Fertilizers